Amperometric Gas detection: A Review - Xiong, L; Compton, R (Electrochemical Science Group, 2014)
Recent progress in amperometric electrochemical gas sensing is reviewed. Topics covered include the use of room temperature ionic liquids (RTILs) as solvents in gas sensors, the advantageous use of micro-electrodes rather than macro-electrodes, membrane free devices and intelligent gas sensors including the simultaneous monitoring of temperature and humidity via voltammetric methods.